A WIN-WIN MODEL OF DEVELOPMENT: HOW INDIAN ECONOMICS REDEFINED UNIVERSAL DEVELOPMENT FROM AND AT THE MARGINS, 1870–1905. Issue 4 (5th December 2021) - Bach, Maria
Abstract : In this article, I argue that looking at lesser known intellectuals can help the history of economics to uncover new ways of seeing the world. My focus is the beginnings of "Indian economics" and its conceptualization of development. The Indian economists, despite their elite status in India, were from an imperial context where they were never considered economists. Studies throughout the twentieth century continued to treat them only as nationalists, rarely as contributors to economic knowledge. My research gives agency to these economists. I show how the position of Indian economics from the margins of discursive space offered a unique perspective that enabled it to innovate at the margins of development discourse. Indian economics redefined the concept of universality in the existing nineteenth-century idea of development by rejecting the widely accepted comparative advantage model and assertion that progress originated in Europe. Moreover, the economists pushed for universal industrialization, even for imperial territories, arguing that universal progress was beneficial to all.